The uncertain web web development in a changing landscape - Larsen, Rob (O'Reilly Media, 2015)
What's the best way to develop for a Web gone wild? That's easy. Simply scrap the rules you've relied on all these years and embrace uncertainty as a core tenet of design. In this practical book, veteran developer Rob Larsen outlines the principles out what he calls The Uncertain Web, and shows you techniques necessary to successfully make the transition. By combining web standards, progressive enhancement, an iterative approach to design and development, and a desire to question the status quo, your team can create sites and applications that will perform well in a wide range of present and future devices.